Larval fat body cells die during the early pupal stage in the frame of metamorphosis remodelation in Bombyx mori - Yu Kaneko (2018)
In holometabolus insects, morphology of the larval fat body is remodeled during metamorphosis. In higher Diptera, remodeling of the fat body is achieved by cell death of larval fat body cells and differentiation of the adult fat body from primordial cells. However, little is known about remodeling of the fat body at pupal metamorphosis in Lepidoptera. In this study, we found that cell death of the larval fat body in Bombyx mori occurs at shortly after pupation. About 30% of the fat body cells underwent cell death on days 1 and 2 after pupation. The cell death involved genomic DNA fragmentation, a characteristic of apoptosis. Surgical manipulation and in vitro culture of fat body cells revealed that 20-hydroxyecdysone and juvenile hormone had no effect on either initiation or progression of cell death. During cell death, a large increase in activity of caspase-3, a key enzyme of cell death, was observed. Western blot analysis of the active form of caspase-3-like protein revealed that the length of caspase-3 of B. mori was much larger than that of caspase-3 in other species. The results suggest that larval fat body cells of B. mori are removed through cell death, which is mediated by a caspase probably categorized in a novel family. © 2011 Elsevier Ltd.